iGenIS 2.0 portal– I-generation information skills portal - Mohd Helmi, Mohd Firdaus; Mohamad Tanuri, Zati Atiqah; Hassim, Hasniza; Tarsik, Nor Famiza; M Said, Salasiah (Universiti Teknologi MARA, Kedah, 2017)
Numerous information was published every day whether in electronic form or printed form. Potential demand of information is unlimited. Every day, all sort of request for information is there. Therefore, as a student they need to be information literate. Information literate defined as ability to identify, locate, evaluate, and select information in all formats to use the information effectively. Due to this situation, iGenIS (i-Generation Information Skills) portal provides alternative method to assist and guide students to know and understand the techniques in searching reliable information. iGenIS Portal is interactive portal which provide useful information for student, especially in learning information skills. The iGenIS portal provides alternative method to assist and guide students to know and understand the techniques in searching reliable information. iGenIS Portal is an interactive portal which provide useful information for student, especially in learning information skills. Techniques in information searching, plagiarism info, citation notes are among vital information embedded in iGenIS portal. Furthermore, it is the first collaborative of interactive information skills portal involving academicians that implement information skills classes to the group of students.